2017
DOI: 10.1038/s41598-017-18124-0
|View full text |Cite
|
Sign up to set email alerts
|

The sleep EEG spectrum is a sexually dimorphic marker of general intelligence

Abstract: The shape of the EEG spectrum in sleep relies on genetic and anatomical factors and forms an individual “EEG fingerprint”. Spectral components of EEG were shown to be connected to mental ability both in sleep and wakefulness. EEG sleep spindle correlates of intelligence, however, exhibit a sexual dimorphism, with a more pronounced association to intelligence in females than males. In a sample of 151 healthy individuals, we investigated how intelligence is related to spectral components of full-night sleep EEG,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 87 publications
3
29
2
Order By: Relevance
“…(2) underlying diagnosed or undiagnosed neurological or psychiatric diseases; (3) general medical health, including diabetes and small vessel cerebrovascular disease; (4) there are substantial genetically-determined stable inter-individual differences in the EEG; (5) exposure to environmental insults. Further studies are needed to clarify the relative contributions of the various types of neurophysiological factors, and to measure the association between EEG-based brain age and various outcomes, such as cognitive performance (Steffener et al, 2016), intelligence (Ujma et al, 2017) and survival . The deviations suggest that there are unobserved factors, such as diet, exercise and diseases, to further explain the variance.…”
Section: Discussionmentioning
confidence: 99%
“…(2) underlying diagnosed or undiagnosed neurological or psychiatric diseases; (3) general medical health, including diabetes and small vessel cerebrovascular disease; (4) there are substantial genetically-determined stable inter-individual differences in the EEG; (5) exposure to environmental insults. Further studies are needed to clarify the relative contributions of the various types of neurophysiological factors, and to measure the association between EEG-based brain age and various outcomes, such as cognitive performance (Steffener et al, 2016), intelligence (Ujma et al, 2017) and survival . The deviations suggest that there are unobserved factors, such as diet, exercise and diseases, to further explain the variance.…”
Section: Discussionmentioning
confidence: 99%
“…Intelligence was shown to correlate positively with NREM sleep EEG sleep spindle activity (Bódizs et al, 2005). Although, a recent metaanalysis casts doubt on the sexual dimorphism of this relationship (Ujma, 2018), the dataset we analyse in our current report is characterized by a clear difference among women and men: women were characterized by positive correlation between sleep spindle amplitude/power and IQ, whereas null correlations were reported for men (Ujma et al, 2014; Ujma et al, 2017). As our current analyses are based on the same dataset, we hypothesize (H6) that P Peak (f maxPeak ) values of the sleep spindle range (9–18 Hz) correlate positively with IQ in women, but not in men.…”
Section: Introductionmentioning
confidence: 56%
“…Here we reveal a positive correlation between whitened spectral peak amplitude of sleep spindle frequency activity during NREM sleep and IQ in women, but not in men (Table 4; Fig 3). Intelligence was shown to be reflected in the intensity (amplitude and/or density) of phasic sleep spindle events or alternatively in the spectral power of sleep spindle frequency activity during NREM sleep (Bódizs et al, 2005; Ujma et al, 2014, Ujma et al, 2017; Ujma, 2018). In the database we use in our present study a marked sexual dimorphism of this effect was also revealed: women but not men were shown to be characterized by the sleep spindle amplitude/power vs IQ correlations (Ujma et al, 2014; Ujma et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations